2015
DOI: 10.3855/jidc.5245
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tularemia during pregnancy

Abstract: This item has no abstract. Follow the links below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Use of gentamicin, ciprofloxacin, and doxycycline is not associated with increased risk for birth defects, stillbirth, premature birth, or low birth weight (12,13). A previous case indicated that during pregnancy, dacryocystitis and abscess on the neck with pharyngitis did not affect the pregnancy outcome after surgical and antimicrobial treatment (15). The gradient of symptoms and clinical manifestations of tularemia in pregnant women differ and depend on the mode of transmission of the infection, the amount and virulence of the pathogen, and the host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Use of gentamicin, ciprofloxacin, and doxycycline is not associated with increased risk for birth defects, stillbirth, premature birth, or low birth weight (12,13). A previous case indicated that during pregnancy, dacryocystitis and abscess on the neck with pharyngitis did not affect the pregnancy outcome after surgical and antimicrobial treatment (15). The gradient of symptoms and clinical manifestations of tularemia in pregnant women differ and depend on the mode of transmission of the infection, the amount and virulence of the pathogen, and the host immunity.…”
Section: Discussionmentioning
confidence: 99%